STRATEGI KIAI KAMPUNG DALAM PENINGKATKAN BACA TULIS AL-QUR’AN (BTQ) SANTRI MUSHOLLA AL-IKHLAS DI DUSUN PLAWANGAN RT.010 RW. 006 DESA GROBOGAN KECAMATAN KEDUNGJAJANG KABUPATEN LUMAJANG - Hairul Ulum; Muhammad Husen (P3M Sekolah Tinggi Agama Islam Miftahul Ulum, 2022)
This study aims to contribute to the guidance of reading andwriting the Qur'an at the Al-Ikhlas Mosque in Plawangan hamlet RT.010 RW.06 Grobogan Village, Kedungjajang District,Lumajang Regency. Kedungjajang, Lumajang Regency uses aqualitative approach with the aim of finding real data inaccordance with existing conditions. The data collection methodused in this research is the method of observation, interviews anddocumentation. Data analysis was carried out through the stagesof data collection, data reduction, data presentation and finallyverification or conclusion. Based on the research, it can beconcluded that: Strategies in increasing the ability to read andwrite the Qur'an according to the law of recitation in Al-IkhlasMosque, namely Kiai and Asatidz in the prayer room prepare byconceptualizing and designing in the form of determining thegoals to be achieved. This is done so that the steps taken by KiaiKampung are clear and in accordance with the expected direction.Increasing the ability to learn to read and write the Qur'an at AlIkhlas Mosque, which is to conduct coaching for Asatidz in AlIkhlas Mosque, the need to use innovative and varied methodssuch as learning while playing and students are also often invitedto study outdoors so that students do not feel bored in teachingand learning activities to read and write the Qur'an.